4-year recurrence risk factors after tension-free vaginal tape-obturator as a treatment of stress urinary incontinence - S, De Miguel Manso; E, García García; JA, Gobernado Tejedor; CE, Badillo Bercebal; D, Viruega Cuaresma; JI, González Martín (Clinical Journal of Obstetrics and Gynecology, 2020)
Objectives: Tension-free vaginal tapes are the gold standard of the surgical treatment of stress urinary incontinence (SUI); however, long-term recurrence of SUI after this surgery has been a matter of problem. Here, we attempted to determine the incidence of its recurrence and to identify the risk factors of 4-year-recurrence of SUI after this surgery. Methods: Of all patients undergoing this surgery (n = 341, 2015-2019), 71 patients were met the study inclusion criteria. Of 71, SUI recurred in 8 patients, with the recurrence rate being 11.3%. The following three were identified to be independent risk factors: older age, history of delivery of macrosomic baby (>4 kg), and the presence of mixed urinary incontinence. The frequency of recurrence in cases with mixed incontinence amounted for 19.5%. Recurrence was 22 and 50% for women with macrosomic delivery once and more than twice, respectively. Conclusion: Advanced age, macrosomic delivery and mixed urinary incontinence have shown to be independent risk factors of recurrence of SUI after tension-free vaginal tape-obturator at 4 years. Key message: Stress urinary incontinence can recur so investigate possible risk factors is a priority. Our paper relates recurrence with: advanced age, fetal macrosomia and mixed incontinence.